Ethical Issues of Digital Transformation - Klein, Amarolinda Zanela (Organizações & Sociedade, 2022)
Ethical issues are involved in the increasing use of emerging technologies by organizations. Several business forums and academic research have been exploring the relationship between ethics and digital transformation, as digital technologies are essential for the so-called Fourth Industrial Revolution, which combine the use of technologies, such as artificial intelligence, machine learning, robotics, blockchain, and neuro and biotechnologies, to create numerous innovations in products, services, and business models. The issue is that these technologies advance at a much faster pace than human institutions, and clarifying how they can be applied to bring development for all, while preserving inalienable human rights, becomes necessary. Thus, in this editorial, we will address important aspects about the ethical issues of digital transformation and propose a series of issues for future studies.